THE DEVELOPMENT OF MEDIA LITERACY FOCUS IN INDONESIA: A LITERATURE STUDY 2016-2021 - Prakoso, Septyanto Galan; Putra, Ferdian Ahya Al; Shidqi, Zia’ulhaq As (International Journal of Humanity Studies (IJHS), 2024)
The development of media literacy can be said as a certain indicator of understanding the current situation and development of a nation. It is understandable if a focus on a certain topic that is related or discussed together with media literacy is worth observing as a parameter to catch a glimpse of a country’s citizens' level of knowledge. Questions about how the development of media literacy in Indonesia is based on related publications are important. This research examines using a literature study about the development of media literacy in Indonesia, by observing the keywords, terms, and focus on publications that correlated with media literacy in Indonesia that were recorded in Google Scholar from 2016 to 2021 and visualized by the Vos viewer program is used to visualize the data and provide a ground base for the findings. The result from this study indicates that media literacy in Indonesia is still not independent as it comes with a certain focus/trend that happens in the country. While the media literacy focus is synchronized with the real-time condition in Indonesia, it also shows that the level of knowledge from the Indonesian people is heavily driven by the media.